Certain actions from the functional movement screen do not provide an indication of dynamic stability - Lockie, R. G.; Callaghan, S. J.; Jordan, C. A.; Luczo, T. M.; Jefriess, M. D.; Jalilvand, F.; Schultz, A. B. (Journal of Human Kinetics, 2015)
Dynamic stability is an essential physical component for team sport athletes. Certain Functional Movement Screen (FMS) exercises (deep squat; left- and right-leg hurdle step; left- and right-leg in-line lunge [ILL]; left- and right-leg active straight-leg raise; and trunk stability push-up [TSPU]) have been suggested as providing an indication of dynamic stability. No research has investigated relationships between these screens and an established test of dynamic stability such as the modified Star Excursion Balance Test (mSEBT), which measures lower-limb reach distance in posteromedial, medial, and anteromedial directions, in team sport athletes. Forty-one male and female team sport athletes completed the screens and the mSEBT. Participants were split into high-, intermediate-, and low-performing groups according to the mean of the excursions when both the left and right legs were used for the mSEBT stance. Any between-group differences in the screens and mSEBT were determined via a one-way analysis of variance with Bonferroni post hoc adjustment (p < 0.05). Data was pooled for a correlation analysis (p < 0.05). There were no between-group differences in any of the screens, and only two positive correlations between the screens and the mSEBT (TSPU and right stance leg posteromedial excursion, r = 0.37; left-leg ILL and left stance leg posteromedial excursion, r = 0.46). The mSEBT clearly indicated participants with different dynamic stability capabilities. In contrast to the mSEBT, the selected FMS exercises investigated in this study have a limited capacity to identify dynamic stability in team sport athletes.